AF-2 activity and recruitment of steroid receptor coactivator 1 to the estrogen receptor depend on a lysine residue conserved in nuclear receptors - Henttu, P M; Kalkhoven, E; Parker, M G (Molecular and cellular biology, 1997)
Hormone-dependent transcriptional activation by nuclear receptors depends on the presence of a conserved C-terminal amphipathic alpha-helix (helix 12) in the ligand-binding domain. Here we show that a lysine residue, which is conserved in most nuclear receptors in the predicted helix 3, is also required for estrogen-dependent transactivation. The replacement of lysine 366 with alanine appreciably reduced activation function 2 (AF-2) activity without affecting steroid- or DNA-binding activity in the mouse estrogen receptor. The mutation dramatically reduced the ability of the receptor to bind steroid receptor coactivator 1 (SRC-1) but had no effect on receptor-interacting protein 140 (RIP-140) binding, indicating that while their sites of interaction overlap, they are not entirely consistent and in keeping with the proposal that the recruitment of coactivators, such as SRC-1, is required for AF-2 activity. Although the function of RIP-140 remains to be established, RIP-140 appears to be capable of recruiting the basal transcription machinery, since overexpression of the protein markedly increased the transcriptional activity of the mutant receptor. Since the lysine residue is conserved, we propose that it is required, together with residues in helix 12, to form the surface by which members of the nuclear receptor family interact with coactivators.